Cyst‐motile stage relationship and molecular phylogeny of a new freshwater dinoflagellate Gymnodinium plasticum from Plastic Lake, Canada. Issue 4 (28th July 2017) - Wang, Na; Luo, Zhaohe; Mertens, Kenneth N.; McCarthy, Francine M.G.; Gu, Li; Gu, Haifeng
SUMMARY: The dinophyceaen genus Gymnodinium was established with the freshwater species G. fuscum as type. According to Thessen et al . (2012), there are 268 species, with the majority marine species. In recently published molecular phylogenies based on ribosomal DNA sequences, Gymnodinium is polyphyletic. Here, a new freshwater Gymnodinium species, G. plasticum, is described from Plastic Lake, Ontario, Canada. Two strains were established by incubating single cysts, and their morphology was examined with light microscopy and scanning electron microscopy. The cyst had a rounded epicyst and hypocyst with a wide cingulum and smooth surface. Vegetative cells were characterized by an elongated nucleus running vertically and a deep sulcal intrusion. The apical structure complex was horseshoe‐shaped and consisted of two pronounced ridges with a deep internal groove, encircling 80% of the apex. Small subunit ribosomal DNA (SSU rDNA), large subunit ribosomal DNA (LSU rDNA) and internal transcribed spacer (ITS) sequences were obtained from cultured strains. Molecular phylogeny based on concatenated SSU, LSU and ITS sequences supports the monophyly of the Gymnodiniales sensu stricto clade but our results suggest that many Gymnodinium species might need reclassification. Gymnodinium plasticum is closest to Dissodinium pseudolunula in our phylogeny but distant from the type species G. fuscum, as are the other gymnodiniacean taxa.